Assessing company strength in South Africa using value added: 1990-2000 - C. King; W. D. Hamman (South African Journal of Business Management, 2004)
This article aims to determine if value added-based ratio analysis could be used to measure organisation strength and be useful as a tool in corporate strategy formulation. The areas of investigation included productivity of production factors, reinvestment in capital and overall business control.Productivity measurement provides insight into the capital and labour intensity of organisations. Some organisations were able to exert high value added to sales ratios, but they did not perform as well when their productivity levels were measured. Reinvestment in capital tries to establish if organisations have the means to uphold and strengthen their present asset base, which also includes its human capital. Margins on sales and value added are used to measure overall business control and provide insight into the ability of organisations to add value through their own production skills or by command of lucrative contracts with suppliers. Organisations that are able to show high values on both ratios are said to display a high degree of overall business control.The formulas used in this article are a replication of those used by the mentioned authors. The models as developed by Bryant are specifically used to see how they fit in the South African context and to draw conclusions about their use for future purposes.
Keywords: 650